New Organometallic Imines of Rhenium(I) as Potential Ligands of Gsk-3 Beta: Synthesis, Characterization and Biological Studies - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A; Muñoz-Osses, M; Muñoz-Osses, M (ROYAL SOC CHEMISTRY, 2018)
Substituted amino-piperazine derivatives were synthesized and used as precursors for the preparation of a series of new organometallic Re(I) imine complexes with the general formula [(eta(5)-C(5)H(4)CHvN-(CH2) 5Pz-R) Re(CO)(3)] (Pz-R: -alkyl or aryl piperazine). The piperazine-based ligands were designed to be potential inhibitors of GSK-3 beta kinase. All the ligands and complexes were fully characterized and evaluated against the HT-29 and PT-45 cancer cell lines, in which GSK-3 beta plays a crucial role. In this context, we carried out biological evaluation using the MTT colorimetric assay. In terms of structure activity relationship, our findings indicated improved biological activity when aromaticity increased in the organic ligands (3d). In addition, the presence of the rhenium fragment in the imines (5a-d) leads to better activity with IC50 values in the range of 25-100 mu M. In addition, our experimental studies were complemented by computational studies, where the volume and electrostatic surface of the organic ligands and organometallic compounds as well as their binding to the kinase protein are calculated.